Studi Komparatif Kriteria Amil Zakat, Hak dan Kewajibannya Pada Lembaga Amil Zakat Nasional (LAZNAS) Di Indonesia (UIN Sunan Kudus, 2020)
This study attempt to conduct an in-depth analysis related to the criteria of Amil zakat, along with their rights and obligations in the context of Islamic history and in this contemporary era, especially in LAZISMU Malang City and LAZNAS Nurul Hayat Malang Branch. This research is descriptive qualitative with data collection methods using documentation and interview techniques. Data analysis in this study uses content analysis techniques. The result of the study is that there are differences between Amil zakat criteria and Amil zakat obligations in the past and present, this can be seen in the criteria of Amil zakat in the past including; freeman (not slaves), amanah, trustworthy, restraint, inclined towards goodness, always giving advice. While today, among them are: having the will, accepting guidance, not smoking (for men), understanding Islam, be able to read the Qur'an. On the other hand, Amil zakat in our era depends on the status of the Amil zakat staff concerned, whether the Amil zakat is full-timer or partimer. However, basically, there are similarities between the rights of Amil zakat the past and the presentday, such as the right of Amil which depends on the proportion of Amil’s performance or one-eighth (12.5%) of the collected zakat funds